(untitled) (Journal of Population and Development, 2022)
This study aims at assessing the utilization of maternal health care service in province 2. Maternal health still remains a public health problem in province 2 though it has been improving in the last decade since the number of women seeking antenatal care has increased. This study helps to analyze the pregnancy risk can be identified, control, managed and contributes to reducing factor the maternal mortality. This study is based on data of Nepal Demographic and Health Survey 2016. The sample size consists of 571 currently married women, age groups 15-49 who had a live birth in the 5 years preceding the survey. This study showed that dependent variables means women who had attend ANC as 4 or more visits and the women who had attended ANC as less than 4 times visits. In this study the utilization of maternal health care based on factors like women’s age, level of education, poor wealth quintile are responsible. In province 2, fewer women are using ANC services. In order to address the existing gap and variation in ANC service utilization, particular attention should be given to women from less education, poor wealthquintile, utilization of services among older age group. In province 2, ANC visit and 4 times is highest of age group 35-49 (44%) followed by 25-34 age group (31%) and least of age group 15- 24 (29%) mothers are using ANC services. While talking about education level, near about one third percent (32%) of respondents do not have any formal education. These factors still make problem to mothers using of ANC services .Special emphasis on women’s education plays a vital role to increase the utilization of maternal health care. This study put forward the need for efforts from government and other agencies should implement the proper policies and programs to bring an improvement in the use of maternal health care services in Nepal.